Immune Responses after a Third Dose of mRNA Vaccine Differ in Virus-Naive versus SARS-CoV-2– Recovered Dialysis Patients. Issue 7 (July 2022) - Attias, Philippe; Azzaoui, Imane; El Karoui, Khalil; de La Selle, Andréa; Sokal, Aurélien; Chappert, Pascal; Grimbert, Philippe; Fernandez, Ignacio; Bouvier, Magali; Samson, Chloé; Dahmane, Djamal; Rieu, Philippe; et al.
Visual Abstract: Abstract : Background and objectives: After two doses of mRNA vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), patients on dialysis show a defective humoral response, but a third dose could increase anti–SARS-CoV-2 spike IgG titers. Responses could be different in virus-naive and SARS-CoV-2–recovered patients on dialysis. However, characterization of memory B cell response after three doses is lacking. Design, setting, participants, & measurements: We evaluated the dynamics of antireceptor binding domain IgG titers and antireceptor binding domain memory B cells until 6 months after two and three doses (administered within 6 months after the second dose) of mRNA vaccine in SARS-CoV-2–recovered and virus-naive dialysis populations. Results were analyzed by ordinary one-way ANOVA, the Kruskal–Wallis test, or the Wilcoxon matched-pairs test as appropriate. Results: In total, 108 individuals (59 patients on dialysis and 49 controls) were included. In virus-naive patients on dialysis, antireceptor binding domain IgG response was quantitatively lower after two doses compared with healthy controls, but IgG titers increased by three-fold after three doses ( P =0.008). In SARS-CoV-2–recovered patients on dialysis, antireceptor binding domain IgG titers after two doses were significantly higher compared with virus-naive patients on dialysis but did not significantly increase after a third dose. Regarding memory B cell response, we detected receptor binding domain–specific memory B cells at similar proportions in virus-naive patients on dialysis and vaccinated controls after two doses. Moreover, a strong receptor binding domain–specific memory B cell expansion was observed after the third dose in virus-naive patients on dialysis (5.5-fold; P <0.001). However, in SARS-CoV-2–recovered patients on dialysis, antireceptor binding domain memory B cells remained unchanged after the third dose. Conclusions: The third dose of mRNA vaccine given within 6 months after the second dose boosts serologic and memory response in virus-naive patients but not in SARS-CoV-2–recovered patients on dialysis. Clinical Trial registry name and registration number: COVID-19: SARS-CoV-2 Specific Memory B and T-CD4+ Cells (MEMO-COV2), NCT04402892